2018
DOI: 10.1002/adma.201707122
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Synergistic Nanoarchitecture Exhibiting Highly Stable and Ultrafast Sodium‐Ion Storage

Abstract: Conversion-type anodes with multielectron reactions are beneficial for achieving a high capacity in sodium-ion batteries. Enhancing the electron/ion conductivity and structural stability are two key challenges in the development of high-performance sodium storage. Herein, a novel multidimensionally assembled nanoarchitecture is presented, which consists of V O nanoparticles embedded in amorphous carbon nanotubes that are then coassembled within a reduced graphene oxide (rGO) network, this materials is denoted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
66
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 125 publications
(66 citation statements)
references
References 48 publications
0
66
0
Order By: Relevance
“…Besides, the incorporation of Li and Mg into the transition metal layer can improve the structural stability and obtain better electrochemical performance . Some pioneers have confirmed that reasonable geometrical structure is also of great importance to improve Na + kinetics . In this case, an optimal bifunctional modulation combining the advantages of chemical substitution and structure design might realize both excellent rate capability and long cycle stability.…”
mentioning
confidence: 99%
“…Besides, the incorporation of Li and Mg into the transition metal layer can improve the structural stability and obtain better electrochemical performance . Some pioneers have confirmed that reasonable geometrical structure is also of great importance to improve Na + kinetics . In this case, an optimal bifunctional modulation combining the advantages of chemical substitution and structure design might realize both excellent rate capability and long cycle stability.…”
mentioning
confidence: 99%
“…[19][20][21][22][23] Amongst, most works have focused on the oxides of Fe, Co and Ni and achieved good results. [28][29][30][31][32] Especially, the monoclinic VO 2 , which has a bilayer structure with large lattice spacing and high capacity has been widely investigated. [28][29][30][31][32] Especially, the monoclinic VO 2 , which has a bilayer structure with large lattice spacing and high capacity has been widely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27] Indeed, other materials like the vanadium oxides are also promising anode materials because of their low cost, high theoretical capacity and the abundant supply of vanadium resource. [28][29][30][31][32] Especially, the monoclinic VO 2 , which has a bilayer structure with large lattice spacing and high capacity has been widely investigated. [13,31,33] Manthiram et al demonstrated a one-step microwave-assisted solvothermal method to prepare one-dimensional VO 2 /rGO nanorod.…”
Section: Introductionmentioning
confidence: 99%
“…Binary traditional metal oxide nanodots (BMO NDs, diameter: 2–20 nm) show merits for catalysis, supercapacitors, lithium‐ion batteries (LIBs) in terms of the more active sites, superior conductivity, shortened ion diffusion distance and high surface area . However, the high surface area of BMO NDs aggravates self‐aggregation, leading to the loss of active sites and the increase in interface charge transfer resistance . Graphene oxide (GO), as a two‐dimensional (2D) substrate, is employed to anchor zero‐dimensional (0D) BMO NDs to prevent the self‐aggregation and increase electron conduction, largely improving their electrochemical performance .…”
Section: Introductionmentioning
confidence: 99%
“…[1] However,t he high surfacea rea of BMO NDs aggravates self-aggregation, leadingt ot he loss of active sites and the increase in interface charget ransfer resistance. [2] Grapheneo xide (GO), as at wo-dimensional (2D) substrate, is employed to anchorz ero-dimensional( 0D) BMON Ds to prevent the self-aggregation and increase electron conduction, largely improving their electrochemical performance. [3] Dependingo nt he electrostatic adsorption between metal cations and the surface functional groups( hydroxyl and carboxyl) of GO, [4] and subsequent nucleation and growth processes, [5] various wet-chemistry methods, including immersion-annealing, water bath, hydrothermal/solvothermal, were used to synthesize the monometallico xide NDs@GO (e.g.,C oO, [6] SnO 2 , [3b] Fe 2 O 3 , [7] TiO 2 / SnO 2 , [8] FeOOH, [9] and so forth) and cation-type BMO NDs@GO, (e.g.,M nFe 2 O 4 , [10] ZnCo 2 O 4 , [11] CoFe 2 O 4 , [12] and so forth).…”
Section: Introductionmentioning
confidence: 99%